Intertextual elements in the discourse of official documents of the Russian Orthodox Church and their translation into English - A.V. Naumova (Язык и текст, 2025)
The purpose of this article is to examine the intertextuality present in the official documents of the Russian Orthodox Church, focusing on its role in preserving theological continuity and cultural heritage. The primary method involves analyzing precedent phenomena, such as references to the Holy Scriptures, writings of the Church Fathers, and canonical decrees, which are instrumental in shaping ecclesiastical doctrine. Special attention is given to the challenges of translating these intertexts into English, particularly in maintaining symbolic depth, spiritual complexity, and conveying culturally significant associations that resonate within the original religious tradition.